In silico investigation and potential therapeutic approaches of natural products for COVID-19: Computer-aided drug design perspective - Rahman, Md. Mominur; Islam, Md. Rezaul; Akash, Shopnil; Mim, Sadia Afsana; Rahaman, Md. Saidur; Emran, Talha Bin; Akkol, Esra Küpeli; Sharma, Rohit; Alhumaydhi, Fahad A.; Sweilam, Sherouk Hussein; Hossain, Md. Emon; Ray, Tanmay Kumar; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a substantial number of deaths around the world, making it a serious and pressing public health hazard. Phytochemicals could thus provide a rich source of potent and safer anti-SARS-CoV-2 drugs. The absence of approved treatments or vaccinations continues to be an issue, forcing the creation of new medicines. Computer-aided drug design has helped to speed up the drug research and development process by decreasing costs and time. Natural com-pounds like terpenoids, alkaloids, polyphenols, and flavonoid derivatives have a perfect impact against viral replication and facilitate future studies in novel drug discovery. It would be more effective having collaborated between governments, researchers, clinicians, and traditional medicine practitioners' safe and effective thera-peutic research. Through a computational approach, this study aims to contribute to the development of effec-tive treatment methods by examining the mechanisms relating to the binding and subsequent inhibition of SARS-CoV-2 ribonucleic acid (RNA)-dependent RNA polymerase (RdRp). The in silico method has also been employed to determine the most effective drug among the mentioned compound and their aquatic, nonaquatic and pharmacokinetics’ data have been analyzed. The highest binding energy has been reported -11.4 kcal/mol against SARS-CoV-2 main protease (7MBG) in L05. Besides, All the ligand is non-carcinogenic excluded L04, good water solubility, no AMES toxicity. The discovery of preclinical drug candi-date molecules and the structural elucidation of pharmacological therapeutic targets have expedited both struc-ture-based and ligand-based drug design. This review article will assist physicians and researchers in realizing the enormous potential of computer-aided drug design in the design and discovery of therapeutic molecules, and hence in the treatment of deadly diseases.